Integrated Interventions to Tackle Antimicrobial Usage in Animal Production Systems: The ViParc Project in Vietnam - Carrique-Mas, Juan J.; Rushton, Jonathan (Frontiers in Microbiology, 2017)
Antimicrobial usage and antimicrobial resistance (AMR) in animal production is now recognized to be an important contributor to the global problem of AMR. Initiatives to curb indiscriminate antimicrobial use in animal production are currently being discussed in many low- and middle-income countries. Well-designed, scientifically sound interventions aimed to tackle excessive antimicrobial usage should provide scientists and policy makers with evidence of the highest quality to guide changes in policy and to formulate better targeted research initiatives. However, since large-scale interventions are costly, they require careful planning in order not to waste valuable resources. Here we describe the components of the ViParc project (www.viparc.org), one of the first large-scale interventions of its kind to tackle excessive antimicrobial usage in Southeast Asian animal production systems. The project has been formulated as a ‘randomized before-and-after controlled study’ targeting small-scale poultry farms in the Mekong Delta region of Vietnam. It aims to provide farmers with a locally-adapted veterinary support service to help them reduce their reliance on antimicrobials. ViParc has been developed in the backdrop of efforts by the Government of Vietnam to develop a National Action Plan to reduce Antimicrobials in Livestock and Aquaculture. Crucially, the project integrates socio-economic analyses that will provide insights into the drivers of antimicrobial usage, as well as an assessment of the cost-effectiveness of the proposed intervention. Information generated from ViParc should help the Government of Vietnam refine its policies to curb excessive antimicrobial usage in poultry production, while lessons from ViParc will help tackle excessive antimicrobial usage